Basic Construction of Sharia Economic Law Based on Ushul Fiqh Asy-Syafi'i (Critical Analysis of the Book of Ar-Risalah) - Mugni Muhit; Jajang Herawan; Muhammad Yunus (Journal of Social Research, 2023)
Imam Shafi'i was the first to have the latest ideas and ideas of his time regarding the method of extracting Islamic law (Takhrij al-Ahkam), which was systematically poured into a paper entitled Ar-Risalah (letter). This bookkeeping effort was in line with the development of Islamic science at that time. The development of this science occurred during the time of Harun Al-Rashid and culminated in the time of Al-Ma'mun. The birth of the book of Ar-Risalah was the initial phase of the development of ushul fiqh science as a scientific discipline. So this book became the main reference for USHUL experts in the later period in compiling similar works. In the book ar-Risalah, it is found that ash-Shafi'i does not mention the name of his book, and does not even give its own theme to a number of important studies that came to be known as ushul fiqh, he wrote in a broader framework, namely: Kehujjahan as-Sunnah. Ar-Risale is just a treatise written by ash-Shafi'i at the request of al-Mahdi. This Ar-Risale still contains material that is not actually ushul Fiqh, the discussion of ushul fiqh is concentrated on As-Sunnah, Ijma', and Qiya which are solely to deny istihsan. The style of thinking and the factors that intervene in the method of istinbat ash-Shafi'i are commensurate with his educational background, he is one of the Imams of Ahlu as-Sunnah wa al-Jama'ah, who in his fiqhiyyah branch sided with two groups, namely ahlu al-Hadith and ahlu ar-Ra'yi (tawasuth). These two capacities of moderate thinking are what make Ash-Syafi'i so beloved and accepted by the majority of the world's Muslims, especially in Indonesia.